AUDISM, GENDER AND REGIMES OF NORMALIZATION: LANGUAGE, COMPETENCE AND THE PRODUCTION OF DIFFERENCE IN EDUCATION - Gomes Almeida, Wolney (Revista Gênero e Interdisciplinaridade, 2026)
This article critically analyzes the processes through which difference is produced in language by articulating the notions of linguistic competence, diagnosis and regimes of normalization, considering their intersections with gender. Grounded in critical Applied Linguistics, post-structuralist perspectives and gender studies, the study problematizes the concept of competence as an apparently neutral category, highlighting its role as a device of classification and regulation of subjects. It argues that linguistic and educational practices participate in the construction of regimes that define what counts as legitimate language, often producing exclusions shaped by social markers such as gender and sensory condition. In this context, the concept of structural hearingism is mobilized to demonstrate how the centrality of orality and hearing operates as a normative matrix that particularly affects Deaf subjects. Furthermore, the article discusses the role of “isms” as discursive technologies that transform differences into diagnoses, contributing to processes of pathologization. The article concludes by advocating for a linguistic education committed to plurality, epistemic justice and intersectionality